(untitled) (Razi Medical Journal, 2025)
Contraception or birth control is the use of one or more of many methods, devices, chemicals, drugs, or even surgical procedures to prevent pregnancy; it is also known as fertility control. It’s difficult to decide which contraceptive method is the best due to a wide variety of options. Researchers continue to work on finding the perfect convenient, effective, affordable, and safe contraceptive with the knowledge that most contraceptive methods are quite effective if used properly. This study was carried out to gain knowledge on how far women are with the various contraceptive methods and to evaluate their awareness of advantages, disadvantages, problems, and the proper use of each method. The study was carried out in Tripoli city by distributing a questionnaire form along with personal interview of 370 randomly selected women at one major women hospital (Al Jalaa Maternity Hospital) and three clinics (The Maltese Libyan Clinic, Al Massara Clinic, Al Mokhtar Clinic), and Fashlom public Polyclinic, the questionnaire consisted of a mix of close ended, open ended and multiple-choice questions. The study showed that 89 of the participants (38%) relied on the natural methods on the claim that no side effects are associated with them, although such methods are not highly effective in preventing pregnancy. Moreover, many of the study’s participants have either wrong or incomplete information on contraceptives in general; however, others have somewhat correct information. The counseling was mostly carried out by physicians and mainly around determining the type of contraceptive used. Roles of pharmacists as counselors and drug information providers were limited or even absent in most situations.